Tuhan Menurut Ludwig Feuerbach - Xaverius Chandra Hasiholan (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2017)
Ludwig Feuerbach proposes that God in religion is the product of human consciousness. Here the author wants to know how Feurbach came to that. First of all, it is to be demonstrated why Feuerbach discussed the subject of religion. Furthermore, it is shown how Feuerbach came to that God is the result of human consciousness facing its natural limitations in the face of its desire for happiness. With that it is found by Feuerbach that God’s supernatural qualities are nothing but a projection of the natural qualities of man himself. Nevertheless, the religious person is unaware of the self-projection he wore to God by the role of imagination, feeling, and theology. This provokes inquiry about why it happens. At the end of it is given little response to Feuerbach’s claim of God.